2016
DOI: 10.1097/fbp.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the phencyclidine model of schizophrenia and nicotine on total and categorized ultrasonic vocalizations in rats

Abstract: Patients with schizophrenia smoke cigarettes at a higher rate than the general population. We hypothesized that a factor in this comorbidity is sensitivity to the reinforcing and reinforcement-enhancement effects of nicotine. Phencyclidine (PCP) was used to model behavioral changes resembling negative symptoms of schizophrenia in rats. USVs in rats have been used to measure emotional states, with 50 kHz USVs indicating positive states and 22 kHz indicating negative. Total and categorized numbers of 22 and 50 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…This study examined the long-term alterations in acoustic features of 50 kHz vocalizations produced by two drugs of abuse, phencyclidine (PCP) and nicotine. In a previous study, we found that chronic but not acute nicotine increased 50 kHz vocalizations, whereas PCP acutely decreased the total number of vocalizations (Swalve et al, 2016). However, the long-term effects of nicotine on features such as bandwidth and maximum frequency as well as the potential significance of these chronic alterations are unknown.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This study examined the long-term alterations in acoustic features of 50 kHz vocalizations produced by two drugs of abuse, phencyclidine (PCP) and nicotine. In a previous study, we found that chronic but not acute nicotine increased 50 kHz vocalizations, whereas PCP acutely decreased the total number of vocalizations (Swalve et al, 2016). However, the long-term effects of nicotine on features such as bandwidth and maximum frequency as well as the potential significance of these chronic alterations are unknown.…”
Section: Introductionmentioning
confidence: 79%
“…Pre-injections of nicotine were given to each rat 2 h after each habituation day in their home cages to limit the initial aversive effect of nicotine (Bevins and Besheer, 2001). Vocalizations of these animals had previously been used to examine the interaction of nicotine and PCP on total and categorized vocalizations (Swalve et al, 2016). In this experiment, four groups of rats were examined, divided into groups based on drug administration: SAL, SAL-NIC 0.2 mg/kg (NIC2), SAL-NIC 0.4 mg/kg (NIC4), and PCP.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations